1999
DOI: 10.1530/jrf.0.1150251
|View full text |Cite
|
Sign up to set email alerts
|

Populations of granulosa cells in small follicles of the sheep ovary

Abstract: The aim of this study in sheep ovaries was to determine the total number of granulosa cells in primordial follicles and at subsequent stages of growth to early antrum formation. The second aim was to examine the interrelationships among the total number of granulosa cells in the follicles, the number of granulosa cells in the section through the oocyte nucleolus, and the diameter of the oocyte. A third aim was to examine whether proliferating cell nuclear antigen labelling occurred in flattened granulosa cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
138
3
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 17 publications
(26 reference statements)
14
138
3
4
Order By: Relevance
“…In the present study, the ontogeny of formation of the ZP was similar to that in cows (Braw-Tal andYossefi, 1997 andFair et al, 1997b) and ewes (Lundy et al, 1999), in which it appeared as islands of zonal material in secondary follicles with two to three layers of granulosa cells and as a complete PAS-positive ring in follicles with more than three layers of granulosa cells (Fig. 7).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, the ontogeny of formation of the ZP was similar to that in cows (Braw-Tal andYossefi, 1997 andFair et al, 1997b) and ewes (Lundy et al, 1999), in which it appeared as islands of zonal material in secondary follicles with two to three layers of granulosa cells and as a complete PAS-positive ring in follicles with more than three layers of granulosa cells (Fig. 7).…”
Section: Discussionsupporting
confidence: 80%
“…primordial, primary and secondary), was smaller than those observed in ewes (Lundy et al, 1999) and cows (Van Wezel and Rodgers, 1996, Braw-Tal and Yossefi, 1997, but was similar to those observed in humans (Lintern-Moore et al, 1974). However, the mean and range in the number of granulosa cells at the equatorial section were compatible to those described for ewes (Lundy et al, 1999), cows (Braw-Tal and Yossefi, 1997) and humans (Lintern-Moore et al, 1974), even when the diameter of oocytes and follicles was smaller. These differences may be species-specific or due to differences in measurement techniques.…”
Section: Discussionsupporting
confidence: 79%
“…1997Braw-Tal and Yossefi, 1997;Sanchez and Ocampo, 1998;Felipe et al, 1999;Zitny et al, 2004;Reynaud et al, 2009;Songsasen et al, 2009). This also showed that folliculogenesis occurs in prepuberal females as reported by Lundy et al (1999) probably mediated by independient gonadotrophin stimuli or by basal levels (Van Vooris, 1999;Evans, 2003).…”
Section: Discussionmentioning
confidence: 63%
“…Measurements were taken of 30 type 1 primordial follicles per ovary of each animal and all observable healthy follicles of the remaining follicular categories (type 2/primary to type 5/large antral), because of the few number present in all the sections studied. Ovarian follicular structure was described previously in SAFS pups (Katz et al, 2009) as follows and was based on the classification proposed by Lundy et al (1999):…”
Section: Morphometric Analysismentioning
confidence: 99%
See 1 more Smart Citation